2017
DOI: 10.1186/s41021-016-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative and oxidative DNA damage in infection-related carcinogenesis in relation to cancer stem cells

Abstract: Infection and chronic inflammation have been recognized as important factors for carcinogenesis. Under inflammatory conditions, reactive oxygen species (ROS) and reactive nitrogen species (RNS) are generated from inflammatory and epithelial cells, and result in the formation of oxidative and nitrative DNA lesions, such as 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) and 8-nitroguanine. The DNA damage can cause mutations and has been implicated in inflammation-mediated carcinogenesis. It has been estimated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…35 In these inflammatory cells, ROS may cause multiple mutations and generate either mutant stem cells or cancer stem cells, leading to carcinogenesis. 36 Different malignant cells of different cancer, for example, hepatoma cells, express heterogeneity in oxidative stress, directly correlated with the SOD level, and due to the sensitivity of cancer cells to oxidative stress, modulation of SOD has been used as a mechanism to kill cancer cells. 37 In addition, we found that the expressions of TLR4 and NF-κB were negatively correlated along with the levels of SOD, MPO, and GSH, while positively correlating with levels of MDA and ROS.…”
Section: Discussionmentioning
confidence: 99%
“…35 In these inflammatory cells, ROS may cause multiple mutations and generate either mutant stem cells or cancer stem cells, leading to carcinogenesis. 36 Different malignant cells of different cancer, for example, hepatoma cells, express heterogeneity in oxidative stress, directly correlated with the SOD level, and due to the sensitivity of cancer cells to oxidative stress, modulation of SOD has been used as a mechanism to kill cancer cells. 37 In addition, we found that the expressions of TLR4 and NF-κB were negatively correlated along with the levels of SOD, MPO, and GSH, while positively correlating with levels of MDA and ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Such damage compromises the genomic integrity 1 and poses a serious risk to human health. 2,3 For example, it is involved in carcinogenesis induced by chronic inflammation, 4,5 human prostate, breast, gastric, colorectal, ovarian and lung cancers, melanoma, leukemia, and lymphoma. 6 OS-induced damage to DNA also contributes to neurodegeneration, promoting Parkinson's disease, [7][8][9] Alzheimer's disease, [10][11][12] and sporadic amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…20 RONS can induce DNA damage via elevation of DNA adducts such as ethno-adducts, 7,8-dihydro-8-oxoguanine (8-oxoG) and other mutagenic precursors in vitro and in vivo. 28,29 Our previous studies indicated that H. hepaticus infection in Rag2 −/− mice induced progression of intestinal pathology from inflammation, dysplasia to carcinoma during the duration of infection, and this process is mediated in part by elevated production of NO. 4,20 The increased production of NO as evidenced by elevation of urinary nitrate excretion was correlated with H. hepaticusinduced overexpression of Tnfα and iNos primarily in macrophages and lower bowel epithelial cells in concert with neutrophils.…”
Section: Discussionmentioning
confidence: 99%